2023
DOI: 10.1007/s11356-023-25301-4
|View full text |Cite
|
Sign up to set email alerts
|

Complex effects of dissolved organic matter, temperature, and initial bloom density on the efficacy of hydrogen peroxide to control cyanobacteria

Abstract: Harmful cyanobacterial blooms plague reservoirs and lakes used for a variety of purposes. Chemical controls are frequently used to mitigate the occurrence of cyanobacterial blooms given that many are fast-acting and effective at reducing cyanobacterial abundance. Recent research has identi ed hydrogen peroxide (H 2 O 2 ) as an environmentally-friendly alternative to algaecides that have typically been used, such as copper sulfate. To build on past studies, these experiments sought to further understand how wel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In addition further studies regarding the effectiveness of H 2 O 2 when varying levels of chlorophyll, total suspended solids, and volatile suspended solids are in the water would be helpful for adjusting concentrations of H 2 O 2 for treatment purposes. Buley et al (2023) suggested that the initial algal biomass could impact the effectiveness of H 2 O 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition further studies regarding the effectiveness of H 2 O 2 when varying levels of chlorophyll, total suspended solids, and volatile suspended solids are in the water would be helpful for adjusting concentrations of H 2 O 2 for treatment purposes. Buley et al (2023) suggested that the initial algal biomass could impact the effectiveness of H 2 O 2.…”
Section: Discussionmentioning
confidence: 99%
“…Further it may be selective for killing Microcystis sp.. Many of the studies published on the efficacy of H 2 O 2 were conducted in a laboratory ( Buley et al, 2023 ; Chen et al, 2021 ; Guo et al, 2021 ; Mukai et al, 2019 ), so the effect might differ in field applications.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the microbial diversity and richness of the substrate were significantly greater than those measured for the water sample. Under anaerobic condi- Currently, chemical measures are usually used to regulate the planktonic state of the water, such as the addition of copper sulfate [26,27]. Although the treatment effect is good, there are chemical residues and cost problems.…”
Section: Richness and Diversity Of Microbial Communitiesmentioning
confidence: 99%